H2O single ionization by light particle-impact: fully differential cross sections - Acebal, Emiliano (2020)
Fully differential cross sections for the single ionization of the 1b 1 and 3a 1 orbitals of H2O by electron- and positron-impact are calculated by means of the CDW-EIS model at an impact energy of 81 eV. A proper average procedure over molecular orientations is performed. Main differences between positron- and electron-impact are observed for coplanar geometries in the binary structures. In addition, an enhancement of the binary region and a decrease of the recoil lobe are observed for positron-impact.